Transformation of the Chinese Press in Indonesia Facing a Ban on Publication, 1958-1965 - Olga S. Pratama; Airell Luthfan Ababiel (Warisan: Journal of History and Cultural Heritage, 2025)
This article discusses the transformation of the Chinese press in the face of the Indonesian government's attempt to shut down the press that used permitted fonts during the Guided Democracy era. This research uses historical research methods to analyze the government's actions in trying to shut down the Chinese press and the transformation of the Chinese press to be able to continue publishing in Indonesia. The Chinese press is a newspaper published in Indonesia using the Chinese language and script. There is also a Chinese press that publishes in Malay, which is published by peranakan Chinese living in Indonesia. The Chinese press has experienced two closure attempts by the government, namely in April 1958 and in 1960 which resulted in the Chinese press in Indonesia transforming. The Chinese press continues to publish in Indonesia by transforming into newspapers that use Indonesian names, language and writing.